Materials metrology and standards for structural performance - Dyson, B. F. [ed.]; Loveday, M. S. [ ed.]; Gee, M. G. [ed.] (London Chapman and Hall, 1995)
Materials metrology is the measurement science used for determining materials property data. An essential element is the symbiosis between the understanding of materials behaviour and the development of suit- able measurement techniques which, through the provision of stand- ards, enable design engineers and plant operators to acquire materials data of appropriate precision. This book is concerned only with those aspects of materials metrology and standards that relate to the design and performance in service ofstructuresand consumerproducts. Itdoes not consider their important role in the processing ofmaterials. Theeditorsare grateful for thecommitmentand patience oftheexperts who contributed the various chapters. In addition, help from staffin the Division ofMaterials Metrology, National Physical Laboratory,inassist- ing with the task of refereeing the chapters is gratefully acknowledged. The production of this book was carried out as part of the Materials Measurement Programme of underpinning research financed by the United Kingdom Department ofTrade and Industry. Brian F. Dyson Malcolm S. Loveday MarkG. Gee Division of Materials Metrology National Physical Laboratory Teddington, TWll OLW UK CHAPTER 1 Materials metrology and standards: an introduction B. F. Dyson, M. S. Loveday and M. G. Gee 1. 1 MATERIALS ASPECTS OF STRUCTURAL DESIGN Knowledge concerning the behaviour of materials has always been vital for the success of manufactured products, but never more so than at the present time.
Keywords: Materials -- Standards; Civil engineering; Surfaces (Physics)